2013
DOI: 10.1371/journal.pone.0067538
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PALB2 Gene in BRCA1/BRCA2 Negative Spanish Hereditary Breast/Ovarian Cancer Families with Pancreatic Cancer Cases

Abstract: BackgroundThe PALB2 gene, also known as FANCN, forms a bond and co-localizes with BRCA2 in DNA repair. Germline mutations in PALB2 have been identified in approximately 1% of familial breast cancer and 3–4% of familial pancreatic cancer. The goal of this study was to determine the prevalence of PALB2 mutations in a population of BRCA1/BRCA2 negative breast cancer patients selected from either a personal or family history of pancreatic cancer.Methods132 non-BRCA1/BRCA2 breast/ovarian cancer families with at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 38 publications
4
23
0
2
Order By: Relevance
“…The rate of MMR gene mutations in our cohort, comparable to that in colorectal cancer cohorts, warrants further investigation. Our cohort had no PALB2 or CDK2NA mutation carriers, which is consistent with previous studies that found very low rates of PALB2 and CDKN2A mutations in PC 12, 39, 49, 50, 54-56 . The lack of mutations in APC, PRSS1 , and STK11 does not eliminate the possibility that these genes cause a small proportion of PC.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of MMR gene mutations in our cohort, comparable to that in colorectal cancer cohorts, warrants further investigation. Our cohort had no PALB2 or CDK2NA mutation carriers, which is consistent with previous studies that found very low rates of PALB2 and CDKN2A mutations in PC 12, 39, 49, 50, 54-56 . The lack of mutations in APC, PRSS1 , and STK11 does not eliminate the possibility that these genes cause a small proportion of PC.…”
Section: Discussionsupporting
confidence: 92%
“…In the USA, Canada, and Europe, the frequency of PALB2 deleterious mutations was revealed to vary from 1.1 to 3.4% (8)(9)(10)(11)(12)(13)(14)(15). A total of 4 previous studies have arisen from Asia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the penetrance of mutations in PALB2 varied significantly in different populations, ranging in a 2-30-fold higher risk, as compared to that in non-carriers (Southey et al, 2010;Antoniou et al, 2014;Slavin et al, 2017). Several missense variants with an unknown significance have also reportedly been associated with breast cancer (Blanco et al, 2013;Damiola et al, 2015;Li et al, 2015;Nakagomi et al, 2016), among which L35P was identified as the pathogenic variant in a family with a strong history of breast cancer (Foo et al, 2017).…”
Section: Palb2/fancnmentioning
confidence: 99%